FINITE ELEMENT METHOD FOR PARTITIONING IRREGULAR MIXED TO DISCUSS BORDER CONTROL IN, WITH RESPECT TO THE STABILIZATION IN WAVE EQUATION - Balcazar Huapaya, Claudio Fernando (2013)
One investigates the controllability properties stabilization for the semidiscretizacion in one dimension of wave equation; where in this semidiscretizacion the meshes are not uniforms. The controllability in the boundary studies. A scheme of mixed finite elements is used; and it is constructed a succession of discreet controls Un for the semidiscreet equation of wave. We analyzed the convergence of this succession and test that assuming M- regularity of the meshes, the succession Un it converges to a continuous control.